Transcriptome profiling using RNA-seq to provide insights into foxtail millet seedling tolerance to short-term water deficit stress induced by PEG-6000 - Bing-qin XU; Xiao-li GAO; Jin-feng GAO; Jing LI; Pu YANG; Bai-li FENG (Journal of Integrative Agriculture, 2019)
Foxtail millet (Setaria italica L.) with high drought resistance, is grown widely in arid and semi-arid regions of the world, and it is a new model plant for genetic and molecular studies. To uncover the molecular mechanisms of stress-tolerance in different genotypes of foxtail millet, physiological analyses combined with transcriptional profiling were conducted using a time-course analysis on two foxtail millet genotypes Damaomao (DM) and Hongnian (HN). The genotype DM performed better than HN under water deficiency, with more moderate relative water content (RWC) and chlorophyll decline. Further physiological and RNA-seq investigations revealed that the two genotypes possessed high conservatism in some vital biological pathways which respond to drought stress, involving hormone synthesis, proline, and soluble sugar synthesis, and reactive oxygen species (ROS) metabolism. However, some genes related to these pathways showed different expression profiles. Likewise, the lower malondialdehyde (MDA) content in HN than DM may be explained by the observation that HN contained more activated genes in the ascorbate-glutathione cycle using KEGG pathway analysis. Overall, abscisic acid (ABA) response genes, ROS scavengers which were probably involved in signaling responses, a set of enzymes involved in proline and soluble sugar synthesis, channel protein genes, and transcription factors, encompassed the early strategy of foxtail millet response to drought. These findings provide a comprehensive molecular view of how different foxtail millet genotypes respond to short-term osmotic stress.